2023
DOI: 10.1186/s12978-023-01599-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the COVID-19 pandemic on maternal and neonatal health services in three referral hospitals in Guinea: an interrupted time-series analysis

Abstract: Introduction In sub-Saharan Africa, there is limited evidence on the COVID-19 health-related effect from front-line health provision settings. Therefore, this study aimed to analyse the effect of the COVID-19 pandemic on routine maternal and neonatal health services in three referral hospitals. Materials and methods We conducted an observational study using aggregate monthly maternal and neonatal health services routine data for two years (March 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Overall, 14 studies reported data from four low-income countries ( 34–47 ), 21 studies were focused on 13 lower-middle income countries ( 48–68 ), seven studies were conducted in five upper-middle income countries ( 69–75 ) and three were multi-centred ( 76–78 ). Out of 45 included studies, 11 studies were cross-sectional ( 41 , 45 , 48 , 51 , 55–57 , 65 , 69 , 70 , 76 ), 14 were pre-post studies ( 34 , 38 , 49 , 50 , 52 , 53 , 56 , 62 , 64 , 72–75 , 77 ), nine were time-series ( 35 , 37 , 39 , 43 , 58 , 59 , 67 , 71 , 78 ), five were mixed methods ( 36 , 42 , 47 , 61 , 63 ) and six were qualitative ( 40 , 44 , 46 , 54 , 60 , 68 ). The included studies’ characteristics are summarised in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Overall, 14 studies reported data from four low-income countries ( 34–47 ), 21 studies were focused on 13 lower-middle income countries ( 48–68 ), seven studies were conducted in five upper-middle income countries ( 69–75 ) and three were multi-centred ( 76–78 ). Out of 45 included studies, 11 studies were cross-sectional ( 41 , 45 , 48 , 51 , 55–57 , 65 , 69 , 70 , 76 ), 14 were pre-post studies ( 34 , 38 , 49 , 50 , 52 , 53 , 56 , 62 , 64 , 72–75 , 77 ), nine were time-series ( 35 , 37 , 39 , 43 , 58 , 59 , 67 , 71 , 78 ), five were mixed methods ( 36 , 42 , 47 , 61 , 63 ) and six were qualitative ( 40 , 44 , 46 , 54 , 60 , 68 ). The included studies’ characteristics are summarised in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Even though eight studies highlighted a reduction in the number/proportion of institutional deliveries ( 36 , 49–51 , 56 , 61 , 62 , 67 , 71 ), six reports ( 38 , 43 , 63 , 73–75 ) observed growth and two studies ( 34 , 42 ) did not find any changes with respect to this indicator. The results varied depending on the setting in three multi-centred studies ( 64 , 77 , 78 ), making it difficult to provide a generalised conclusion. Home delivery rate rose based on the results of two studies originated from Mozambique and India ( 36 , 62 ) and reduced in Ghana ( 48 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations